THE MORPHOLOGICAL ANALYSIS OF VOLCANIC RELIEF OF THE REPUBLIC OF ARMENIA FOR THE PURPOSE OF REVEALING BURIED MORPHOSTRUCTURES (Proceedings of the YSU C: Geological and Geographical Sciences, 2003)
The methods of revealing the buried morphostructures in the volcanic regions of Armenia by means of the morphological analysis of the relief and the results of the investigations of many years by the authors for this purpose are discussed in the article.
Keywords: volcanic regions of Armenia; morphological analysis; revealing buried morphostructures